The Influence of Training, Self-Efficacy and Motivation on Employee Performance at CV Mega Motor Cicurug - Azhirni Alpha Khasanah; Samsuri; Tini Kartini (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the influence of training, self-efficacy and motivation on employee performance at CV Mega Motor Cicurug, both simultaneously and partially. The subjects of this research were 48 CV Mega Motor Cicurug employees as sample members. The data analysis technique used in this research uses the IBM SPSS 25 software application. The form of this research is descriptive and verifiable with a quantitative approach. The data analysis method used in this research is multiple linear regression analysis. The research results show that training, self-efficacy, motivation and employee performance meet very good criteria. Simultaneously and partially, training, self-efficacy and motivation have a positive and significant effect on the performance of CV Mega Motor Cicurug employees.